Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1139/apnm-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

Early life undernutrition reduces maximum treadmill running capacity in adulthood in mice

Abstract: Undernutrition during early life causes chronic disease with specific impairments to the heart and skeletal muscle. The purpose of this study was to determine the effects of early life undernutrition on adult exercise capacity as a result of cardiac and skeletal muscle function. Pups were undernourished during gestation (GUN) or lactation (PUN) using a cross-fostering nutritive mouse model. At postnatal day 21, all mice were weaned and refed a control diet. At postnatal day 67, mice performed a maximal treadmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 53 publications
4
15
0
Order By: Relevance
“…The PGR group had impairments in global cardiac function and mass (LV mass, stroke volume, cardiac output, myocardial performance index [MPI]), and diminished diastolic/systolic function (prolonged isovolumetric contraction/relaxation) in adulthood. These findings support the existing DOHaD literature, which has shown that PGR in mice impairs functional capacity of the heart, calcium flux, and exercise capacity, leading to an increased risk for CVD and mortality in adulthood [12,15,17,23,24,[28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionsupporting
confidence: 90%
“…The PGR group had impairments in global cardiac function and mass (LV mass, stroke volume, cardiac output, myocardial performance index [MPI]), and diminished diastolic/systolic function (prolonged isovolumetric contraction/relaxation) in adulthood. These findings support the existing DOHaD literature, which has shown that PGR in mice impairs functional capacity of the heart, calcium flux, and exercise capacity, leading to an increased risk for CVD and mortality in adulthood [12,15,17,23,24,[28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionsupporting
confidence: 90%
“…Starting at PN7, PUN pups displayed growth stunting and were 18% smaller ( P < 0.001) than the CON and GUN mice into adulthood. These observations are consistent with the literature (6,9,11,16). At completion of the investigation (PN70) female mice were smaller than male mice within each diet group (Fig.…”
Section: Resultssupporting
confidence: 94%
“…Cardiac parameters mirrored existing literature (11) with males having a larger left ventricular (LV) volume during diastole ( P = 0.030; Table 1), stroke volume ( P = 0.0105; Table 2), and cardiac output ( P = 0.0129; Table 2) compared with female mice. Females showed a larger LV-anterior wall diameter during diastole ( P = 0.0347; Table 2) and LV-posterior wall diameter during diastole ( P = 0.0125; Table 2).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…On the contrary, the consequences of early life nutrition restriction, especially protein restriction, are far-reaching and influential. For instance, human aging cohort studies have shown that low birth weight due to malnutrition during pregnancy is strongly associated with decreased muscle volume and strength in later life [ 5 , 6 , 7 ]. Besides general overnutrition or undernutrition, overconsumption or deficiency of essential nutrients also stunts organ and tissue development, resulting in later-life risks [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%